Signs of the Times: Medieval Punctuation, Diplomatic Encoding and Rendition - Elisa Cugliana; Gioele Barabucci (Journal of the Text Encoding Initiative)
Digitally managing punctuation in the editions of medieval manuscripts is one of those issues that initially looks like a minor detail, but later reveals itself as a tangled web of problems spanning from computer science (how to represent punctuation signs?) to philology (what types of signs exist?) through epistemology (is the processing of punctuation a mere technical transformation or a valuable part of the scholarship?). The aim of this paper is to address the theoretical aspects of these questions and their practical implications, providing a couple of solutions fitting the paradigms and the technologies of the TEI. This paper describes how we dealt with the encoding and transformation of the punctuation in the Early New High German edition of Marco Polo’s travel account. Technically, we implemented a set of general rules (as XSLT templates) plus various exceptions (as descriptive instructions in XML attributes), and applied them in an automated fashion (using XProc pipelines). In addition to this, we discuss the philological foundation of this method and, contextually, we address the topic of the transformation of a single original source into different transcriptions: from a highly diplomatic edition to an interpretative one, going through a spectrum of intermediate levels of normalization. We also reflect on the separation between transcription and analysis, as well as on the role of the editor when the edition is the output of a semi-automated process.